Internet diffusion vs. the crisis of the new economy - Carlo Tesauro; Domenico Campisi (European Regional Science Association (ERSA), 2002)
The diffusion of Internet in the world, both in terms of 'users' and 'information suppliers' is continuously and constantly increasing. This market growth is based on a development that follows the usual behavior of technological innovation diffusion (S-shaped logistic curve), so it is allowed to obtain reliable forecasts about the future market trend. Nevertheless, despite the continuous growth of the 'target', the E-business seems to be in a crucial situation absolutely unpredictable since few moths ago, when viceversa looked as the main driving force of the 'new economy' attacking the boundaries of the 'global market'. The objective of this paper is to analyze the potentialities of the growing market, through the actual and forecasted number of users, and the condition of the general offer, in terms of typology and quality of the services supplied, trying to identify a reason for this crisis. Keywords: Internet, E-business, Global Market, New economy
Keywords: 330